Effectiveness of TRIZ Invention for Enhancing Design Creativity in High School Students: The role played by teacher self-efficacy - Dongna, Liu; Sharul, Azim Bin Sharudin@Sharaddin (South Asian Journal of Social Sciences and Humanities, 2025)
As education systems evolve to prepare learners for the challenges of the 21st century, there is an earnest need for a holistic educational approach that embraces creativity, innovation, and empowers both teachers and students to offer new insights and creative ideas to survive in the future era. For this purpose, there are different pedagogical interventions such as TRIZ can bring many incumbent benefits and prosperities in the educational context. However, China has a slow pace towards this beneficial strategy and the major reason behind this factor is their conventional conceptions and resistance of teachers and others to embrace new technology. Therefore, this study has proposed a conceptual framework where the study has illuminated previous literature associated with TRIZ, design creativity, teachers’ efficacy and the challenges associated with TRIZ. The study followed a review strategy and explored the last 5 years’ papers to gather relevant empirical information from the research. In conclusion, the study has shared that TRIZ is a radical systematic approach that is a great opportunity for educators and policymakers to transform the Chinese educational system and equip educators and students with design creativity and problem-solving skills. However, this beneficial intervention strategy is confined to different conventional challenges and issues as resistance to innovation.